The Influence of Competence and Social Support on Organizational Citizenship Behavior (OCB) Mediated by Organizational Culture at the Directorate General of Corrections - Miftahus Surur Ramadhan; Yudi Nur Supriadi (Universitas KH. Abdul Chalim Mojokerto, 2025)
Human Resource Management (HRM) plays a central role in shaping employee behavior, including Organizational Citizenship Behavior (OCB). Demonstrating high loyalty and commitment to the organization is a trait expected by all superiors or leaders. Based on initial observations and a brief preliminary survey conducted by the researcher, many employees frequently complain, lack motivation, and show indifference toward their work environment and duties at the Directorate General of Corrections, Ministry of Law and Human Rights of the Republic of Indonesia. This study aims to analyze the influence of competence and social support on Organizational Citizenship Behavior (OCB), with organizational culture as a mediating factor. The study sample consists of 219 employees from the Directorate General of Corrections, Ministry of Law and Human Rights of the Republic of Indonesia, collected through questionnaires and analyzed using a quantitative method with descriptive data analysis techniques utilizing SmartPLS version 3. The findings of this study indicate that competence, social support, and organizational culture significantly influence OCB. Competence and social support also have an impact on organizational culture. Furthermore, organizational culture effectively mediates the relationship between competence, social support, and OCB at the Directorate General of Corrections.